2020
DOI: 10.3390/d12100372
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and pH on the Egg Production and Hatching Success of a Common Korean Copepod

Abstract: The recent accelerated ocean acidification and global warming caused by increased atmospheric carbon dioxide may have an impact on the physiology and ecology of marine animals. This study was conducted to determine the egg production rate (EPR) and hatching success (EHS) of Acartia ohtsukai in response to the combined effects of an increase in temperature and a lower pH. Acartiaohtsukai with fresh surface seawater were collected in the northwestern Yeoja Bay of Korea in September 2017. The temperature and pH c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Studies that measure hatch rate in brooders were limited to crustaceans and molluscs, as hatch rate was not reported for brooding species in any other taxa. Several brooding crustacean species held at low pH were found to have differences in fecundity, hatch success, or number of offspring Mayor et al, 2007;Findlay et al, 2009;Zhang et al, 2011;Vehmaa et al, 2012;Weydmann et al, 2012;Kita et al, 2013;Long et al, 2013;McConville et al, 2013;Zervoudaki et al, 2013;Cripps et al, 2014;Cao et al, 2015;Swiney et al, 2015;Thor and Dupont, 2015;Choi et al, 2016;Miller et al, 2016;Vehmaa et al, 2016;Borges et al, 2018a;Cardoso et al, 2018;Gravinese, 2018;Pansch et al, 2018;Thor et al, 2018;Lee et al, 2020). One study in copepods found that OA reduced the number of brooding females (Lee et al, 2019).…”
Section: Fecundity and Reproductive Outputmentioning
confidence: 99%
“…Studies that measure hatch rate in brooders were limited to crustaceans and molluscs, as hatch rate was not reported for brooding species in any other taxa. Several brooding crustacean species held at low pH were found to have differences in fecundity, hatch success, or number of offspring Mayor et al, 2007;Findlay et al, 2009;Zhang et al, 2011;Vehmaa et al, 2012;Weydmann et al, 2012;Kita et al, 2013;Long et al, 2013;McConville et al, 2013;Zervoudaki et al, 2013;Cripps et al, 2014;Cao et al, 2015;Swiney et al, 2015;Thor and Dupont, 2015;Choi et al, 2016;Miller et al, 2016;Vehmaa et al, 2016;Borges et al, 2018a;Cardoso et al, 2018;Gravinese, 2018;Pansch et al, 2018;Thor et al, 2018;Lee et al, 2020). One study in copepods found that OA reduced the number of brooding females (Lee et al, 2019).…”
Section: Fecundity and Reproductive Outputmentioning
confidence: 99%
“…Acartia ohtsukai, which occurs in the estuarine and coastal waters of Korea, China, Vietnam, and Japan (Razouls et al, 2005(Razouls et al, -2020, is also an excellent candidate live prey species for aquaculture, because it is found in high densities owing to its adaptability to rapid changes in temperature and salinity (Choi et al, 2019;Lee et al, 2020). A. ohtsukai dominates in summer and autumn in Yeoja Bay, comprising more than 60% of the zooplankton community in the inner bays in September (Lee, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Further, some traits, such as egg size, egg volume and the number of eggs per egg sac, did not provide significant information at the assemblage level. However, they could be useful indicators of population functionality when utilised at the species level [73]. Further, our study is observational and does not involve experimental manipulations.…”
Section: Discussionmentioning
confidence: 99%